How Do Patients With Parkinson's Disease Approach Advance Care Planning? A UK-Based Mixed Methods Study. (January 2022) - Churm, Deepta; Dickinson, Claire; Robinson, Louise; Paes, Paul; Cronin, Thomas; Walker, Richard
Background: Advance Care Planning (ACP) allows people the opportunity to plan for a time when they may lose capacity. The aim of this study was to determine the extent people with Parkinson's disease (PD) were aware of ACP, existing plans they held and to explore their own views, as well as their relatives, on planning for the future. Methods: This was a sequential explanatory mixed methods study with a postal quantitative survey to establish awareness and engagement with planning for the future; and qualitative semi-structured interviews to explore the views of people with PD and their relatives on ACP and future plans. Results: 104 questionnaires were analyzed. 76% of respondents had not heard of ACP, while 69% expressed an interest in finding out more about ACP. 78% had a will, and 23% had appointed lasting power of attorneys. All interviewees acknowledged engaging in some aspect of planning. Plans were mostly practical as opposed to health-care related. Interviewees expressed a preference for ACP to be carried out by their PD team, at home, and at a time relevant to their condition. Conclusion: The awareness and understanding of ACP in people with PD is low. While there is desire to be better informed about ACP, this did not translate into desire to engage in ACP. Health professionals should identify people for whom ACP may serve a positive purpose, and proactively address ACP as a continuum with them, while ensuring awareness is raised about ACP, and there is access for who are interested.